Lower Quarter Muscle Activation in Adolescent Tennis Players with and without Lower Back Pain - Immelman, Elandie Elizabeth (My University, 2018)
Background Injury can cause long periods away from active training and if not addressed correctly may lead to recurrent injuries or chronic pain. Approximately 20% of adolescent tennis players suffer from lower back pain. Extrinsic and intrinsic risk factors could contribute to injury in tennis players. The most powerful and strenuous stroke in tennis is the serve. Motor control is crucial during a force-generating stroke such as the tennis serve. Motor control is the result of a harmonious co-activation relationship between muscle groups. The aims of this study were to compare the muscle activation and joint angles of the lower quarter during the different phases of the tennis serve in adolescent tennis players with and without lower back pain. Further aims of this study compared the demographics, active Range Of Motion (ROM) of the lumbar spine and hips, the Star Excursion Balance Test (SEBT) and the relationship between variables in adolescent tennis players with and without lower back pain. Identifying risk factors in the chosen variables could equip the player with an individualised, well-balanced training programme in order to prevent or to rehabilitate an injury. Study Design This study used a cross-sectional, observational design. Method A total of 138 junior tennis players, between the ages of 10 and 18, and who were members of the North Gauteng Tennis Club in 2017, were selected for this research study. Junior tennis players were invited, with no prejudice or pressure, to participate in the study which more specifically included adolescent tennis players who played tennis at least once a week and who had played tennis for at least three years prior to this study. Tennis players were excluded from participating in the study if they had been diagnosed with any acute musculoskeletal injuries, metabolic conditions, spinal fractures, spinal pathology, or had undergone any spinal surgery. Participants completed a self-report questionnaire regarding their demographic history. Physical testing included active ROM and the SEBT. Further physical testing incorporated motion analysis (Inertial Measurement Unit system) and wireless surface electromyography (EMG) during the tennis serve. A total of six service motions were recorded and used for analysis. Seven markers, to detect different phases of the serve, were identified during data processing. The phases were used to analyse the kinematics and muscle activation during the tennis serve at that point. Kinematic analyses of the trunk and bilateral hips were conducted. The rectus abdominis (RA), external obliques (EO), erector spinae (ES) and gluteus maximus (GM) muscles were evaluated during the tennis serve. Lower back pain status was used as the dependent variable. Means and standard deviations were used to describe the demographic history and point of maximum muscle activity. Medians and ranges were used to present active ROM, SEBT, kinematics and muscle activation. The Chi-Square (X²) test was used to look at the differences between the categorical variables, while a Mann-Whitney U test was used to determine the significant differences between the independent variables. A Pearson bivariate correlation analysis was performed to determine the relationships between the significant variables. Furthermore, a binary logistic regression model determined which of the variables found in the correlation was the strongest at predicting whether a participant would be categorised into the Lower Back Pain (LBP) or No Lower Back Pain (NLBP) groups. The Forward Stepwise (Wald) method was used. Results A total of 33 adolescent tennis players from the North Gauteng Tennis Club participated in this study. The sample comprised of 21 participants without lower back pain (the NLBP group: 13.43 ± 2.20 years old) and 12 participants with lower back pain (the LBP group: 14.92 ± 1.98 years old). A significant association was found between lower limb dominance (p=0.015), where the LBP group consisted of significantly more left lower limb dominant tennis players (NLBP two left; 19 right; LBP five left; seven right). There was a significant association between the number of hours played on a hard-court surface and the presence of LBP (p=0.052). All participants reported playing on a hard court and spent an average of 5.86±2.59hrs (NLBP group) and 8.08±3.73hrs (LBP group), per week. Furthermore, compared to the LBP group, the NLBP group spent significantly more time playing other types of sport per week (p=0.045; NLBP 3.48±2.89hrs; LBP 1.42±2.39hrs). The only significant difference found during the active ROM testing was for lumbar lateral flexion to the right. The NLBP group had a significantly greater median range of 36° for right-sided lateral flexion (p=0.012) compared to the 29° for the LBP group. Results from the SEBT indicated differences in the left anteromedial (p=0.011), left anterior (p=0.047), right anterolateral (p=0.010), left posterolateral (p=0.047) and right posterior (p=0.041) reach directions. Differences in joint angles and muscle activation between the two groups were seen in all phases of the tennis serve. The most important findings were in the start point of the preparation phase (PS), the ball release point of the preparation phase (PR), the loading point of the preparation phase (PL) and the finish point of the deceleration phase (DF). Generally, compared to the LBP group, the NLBP group experienced greater muscle activation in the RA and EO muscles during the preparation and acceleration phases. Furthermore, the ES and GM were more active during the preparation phase for the NLBP group. However, the ES was more active in the LBP group for most of the phases (PL to DF). During the end phase of the serve (DF), the LBP group experienced greater activation in the anterior and posterior trunk musculature. The analysis of the kinematics and muscle activation during the tennis serve ascertained the following: (1) The LBP group displayed different levels of muscle activation and different reactions in the kinematic mechanisms in the hips and trunk (i.e. it is proposed that the LBP group used rotatory mechanisms whilst the NLBP group made use of vertical linear mechanisms); (2) The recruitment of motor units was slower in the LBP group; (3) The movement patterns of the trunk and hips in the LBP group were mal-adaptive in terms of shock absorption. The logistic regression displayed three key points that could assist in the identification of risk factors for LBP during the tennis serve. • Firstly, a smaller angle of hip flexion (PS OR=0.75; PR OR=0.62) and external rotation (PR OR=1.406; PL OR=0.866) during the preparation phase; • Secondly, a greater degree of adduction (DF OR=0.533), internal rotation (DF OR=1.252) and flexion (DF OR=1.269) of the hip during the deceleration phase. [These kinematics key points emphasise the importance of force transfer over a stable base of support.]; • Thirdly, the importance of correct muscle activation (concentric and eccentric) of the anterior trunk and control throughout movement during the loading (RA OR=0.645; EO OR=1.101) and deceleration (RA OR=1.537) phases. [The muscle-activity key point emphasises the importance of muscle strength and the global stability functional testing.] Conclusion The results present valuable intrinsic and extrinsic risk factors that could contribute to injury in adolescent tennis players. The focus in this study was on kinematics and muscle activation during the serve. An evaluation of the tennis serve showed that the two groups displayed different preparation and execution strategies regarding the kinematics and muscle recruitment needed to move between the phases. The NLBP group made use of more hip flexion during the serve. In contrast, the LBP group relied more on trunk rotation and lateral flexion during the serve. This can be explained as a vertical linear mechanism versus a rotatory mechanism for force generation and transfer. The NLBP group displayed greater muscle activation in the preparation and acceleration phases. The findings support the theory of pain adaptations and pain inhibition in players with lower back pain. We can conclude that the LBP group made use of a compensatory mechanism in order to adapt to their pain and/or restriction of movement and therefore displayed a lack of motor control. One of the major strengths of this study is that the identification of variables that have an effect on lower back pain status could play an important role in the prevention of injury and in rehabilitation programmes. The three key points need to be kept in mind in the treatment and training of adolescent tennis players. These findings can be used in motor-control re-training and in other rehabilitation programmes. Furthermore, this could impact on the high incidence of lower back pain and chronic pain in the future.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the Degree MSc (Physiotherapy), Gauteng, 2018